Evolution and adaptation of terrestrial plant‐associated Plantibacter species into remote marine environments - Li Liao; Qilong Qin; Dian Yi; Qiliang Lai; Bolin Cong; Huiming Zhang; Zongze Shao; Jin Zhang; Bo Chen (Molecular Ecology, 2024)
Microbes are thought to be distributed and circulated around the world, but the connection between marine and terrestrial microbiomes remains largely unknown. We use Plantibacter , a representative genus associated with plants, as our research model to investigate the global distribution and adaptation of plant‐related bacteria in plant‐free environments, particularly in the remote Southern Ocean and the deep Atlantic Ocean. The marine isolates and their plant‐associated relatives shared over 98% whole‐genome average nucleotide identity (ANI), indicating recent divergence and ongoing speciation from plant‐related niches to marine environments. Comparative genomics revealed that the marine strains acquired new genes via horizontal gene transfer from non‐ Plantibacter species and refined existing genes through positive selection to improve adaptation to new habitats. Meanwhile, marine strains retained the ability to interact with plants, such as modifying root system architecture and promoting germination. Furthermore, Plantibacter species were found to be widely distributed in marine environments, revealing an unrecognized phenomenon that plant‐associated microbiomes have colonized the ocean, which could serve as a reservoir for plant growth‐promoting microbes. This study demonstrates the presence of an active reservoir of terrestrial plant growth‐promoting bacteria in remote marine systems and advances our understanding of the microbial connections between plant‐associated and plant‐free environments at the genome level.